SISU - Sistema de Informação de Sarcomas Uterinos - Nuno Manuel Santos Queiros (2015)
Currently, one of the problems in national oncology institutions is the storage of patient data in paper format, especially earlier patients. Therefore, the information is too scattered and it becomes difficult to access it, which complicates the clinician's daily practice and advances in research. Thus, an application it is required that allows not only a centralization of the information but also the clinician to extract valuable information that may help in the treatment of patients or in clinical studies. This dissertation describes the concept, architecture and features of a system called USIS - Uterine Sarcoma Information System. With USIS, it is intended to take the first step to create a national oncology information system that assists clinicians in their daily clinical practice. USIS is a pilot project, developed in partnership with clinicians of the Portuguese Institute of Oncology of Porto, with uterine sarcomas as the case study and it allows the clinician to manage the information of his patients, to perform customized data queries and to share information with other clinicians. USIS was developed in modules, based on a generic model that provides the system with high levels of flexibility and configurability, thereby allowing to quick and easily expand the system to others pathologies.